การศึกษาการเรียนการสอนวิทยาศาสตร์ระดับมัธยมศึกษาตอนปลาย ในโรงเรียนจุฬาภรณราชวิทยาลัย สังกัดกรมสามัญศึกษา - พัชรินทร์ โพธิผล (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purpose of this research was to study science instruction at the upper secondary education level in Princess Chulabhorn s Colleges under the jurisdiction of the department of general education. The sample used in this research were 12 school administrators, 25 science teachers and 338 students from 8 schools. The data were collected by means of questionnaires, structured interviewed and observation. The obtained data were analyzed by means of percentage, arithmetic moan and content analysis. The research findings were as follows: 1. The administration facilitating science instruction at the upper secondary education level in Princess Chulabhorn s Colleges were 1) The school administrators had set the plans and implemented according to the science instructional development plan. The problem found was the lack of teacher cooperation. 2) In the aspect of instructional media, there was a central media center. 3) In the aspect of measurement and evaluation, there was promotion of developing instrument for measurement and evaluation in the school such as examination bank. 4) In the aspect of the extra curriculum activities, the students could search and study in the library in a longer period of time. 2. The science instruction at the upper secondary education level were 1) Every teachers prepared the lesson plan weekly in advance by themselves, the problem found was that the teachers did not have time in teaching preparation because they had a lot of additional duties besides teaching. 2) In the aspect of instructional activities, most teachers used lecture and experiment. In the experiment preparation, there were laboratory assistants helping in preparing the experimental equipment and took care of all the equipment and chemical substance, the problem found was that the teachers did not have a wide variety of teaching techniques. 3) The instructional media were work sheet information sheet, real things, artefacts and transparencies, the problem found was that the teachers did not have knowledge and skills in media application. 4) In avocet of measurement and evaluation, teachers gave the tests to students after the lesson, most of the measuring and evaluating instruments were objective tests. In addition, there was the practical test to emphasize practical skills, the problem found was that the measuring and evaluating instruments were not standard. 5) In the aspect of extra curriculum activities, every school arranged the activities during science week which was science project, the problem found was that the teachers did not have skills for managing extra curriculum activities.